Design, Physicochemical Characterisation, and Printability Optimisation of a Novel Composite Biomaterial Ink for Extrusionbased 3D Bioprinting: An In-vitro Study - Parkavi Arumugam; R Srivarsan; Kaarthikeyan Gurumoorthy (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Three-Dimensional (3D) bioprinting enables patient-specific regenerative strategies for improved oral health and quality of life, with rational Biomaterial Ink (BI) design being critical for extrusion-based printing as composition governs printability, structural fidelity, and biological relevance. Systematic optimisation is essential for developing BI suitable for oral and craniofacial tissue defects. Aim: To develop a Polyethylene Glycol (PEG) - Polyethylene Glycol Diacrylate (PEGDA) -hydroxyapatite-collagen composite BI and to evaluate its feasibility for extrusion-based bioprinting through phase-wise printability assessment, followed by rheological and surface wettability characterisation. Materials and Methods: The present in-vitro study was conducted at the Department of Biomaterials, Saveetha Dental College, Chennai, Tamil Nadu, India, from February 2023 to March 2023. BI formulations were sequentially developed by varying PEG, PEGDA, hydroxyapatite, and collagen concentrations. Phase-wise printability screening identified formulations with stable extrusion and shape retention. Selected formulations underwent rheological evaluation, printability assessment and surface wettability by contact angle analysis. Contact angle data were analysed using One-way Analysis of Variance (ANOVA) and Tukey's post-hoc test (p